DEVELOPMENT OF TFD BOARD GAME MEDIA TO ENCOURAGE SELF-DISCLOSURE AMONG STUDENTS AT SMA NEGERI 2 TEBING TINGGI (Pena Cendekia Insani, 2026)
School guidance and counseling play a crucial role in the personal, social, academic, and career development of students. One aspect that requires attention is students’ self-disclosure, as this relates to their ability to form interpersonal relationships, receive support, and adapt to the school environment. Observations at SMA Negeri 2 Tebing Tinggi indicate that during group counseling sessions, many students remain silent, passive, and reluctant to share their thoughts or personal experiences, while guidance counselors still rely on conventional methods without specialized supporting media. Results from a needs survey of students in class X-2 showed that 74% of respondents needed interactive, safe, and engaging supporting media to encourage self-disclosure. Based on these needs, this study developed the TFD (Talking, Feeling, Doing) Board Game to encourage students’ self-disclosure in group counseling services. The research method employed a research and development (R&D) approach, comprising expert validation, limited pilot testing, and participant response evaluation. The validation results showed that the media met the criteria for content and design feasibility; the pilot test demonstrated an increase in student participation and self-disclosure during group counseling sessions